Why Ablation of Sites With Purkinje Activation Is Antiarrhythmic: The Interplay Between Fast Activation and Arrhythmogenesis - Coronel, Ruben; Potse, Mark; Haïssaguerre, Michel; Derval, Nicolas; Rivaud, Mathilde R.; Meijborg, Veronique M. F.; Cluitmans, Matthijs; Hocini, Mélèze; Boukens, Bastiaan J. (Frontiers in Physiology, 2021)
Ablation of sites showing Purkinje activity is antiarrhythmic in some patients with idiopathic ventricular fibrillation (iVF). The mechanism for the therapeutic success of ablation is not fully understood. We propose that deeper penetrance of the Purkinje network allows faster activation of the ventricles and is proarrhythmic in the presence of steep repolarization gradients. Reduction of Purkinje penetrance, or its indirect reducing effect on apparent propagation velocity may be a therapeutic target in patients with iVF.